Determination of oil and grease in water discharge from UMK Jeli cafeterias - Nurul Aida Siman (2017)
Oil and Grease (OG) is a measure of a variety of substance including motor oil, cooking oil and fuels. The increasing number of education institution place in Malaysia contributes to the development of food industries such as cafeteria and food stall that produces huge amount of waste that may causing a negative effect towards health and environment if it does not being treated. It is because the waste contain high level of total suspended solid such as oil and grease. The sources of oily water discharged in UMK Jeli come from the 2 cafeterias in UMK Jeli itself. This study was conducted to analyze the concentration of oil and grease in UMK Jeli cafeterias water discharge and nearby river and to compare oil and grease concentration in water discharge from UMK Jeli cafeterias and nearby river with Environmental Quality Act (EQA) standard guideline. This study was conducted by using Hexane Extractable Gravimetric Method. The data for monthly concentration of oil and grease taken from May 2016 to October 2016, in water discharged from all the sampling point which is Medan Selera, IBS Cafe, Lanas River and Gemang River are below 10 mg/l, which is the EQA standard for oil and grease in water effluent. All of the data obtained contained the low concentration of oil and grease in it due to the usage of filter paper during the drainage process of the solvent layer. The filter paper trapped some of the oil contents in the solvent layer which were important in determination of oil and grease. The data shows that the concentration of oil and grease in Medan Selera water discharged are the highest among all the sampling points and affecting the concentration of oil and grease in nearby river which is Lanas River.